2016
DOI: 10.1097/nmd.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stigma on Recovery Attitudes in People With Anorexia Nervosa in Intensive Treatment

Abstract: Self-stigma in individuals with anorexia nervosa (AN) may affect engagement in intensive treatment. The objective of this study was to test a Model of Self-Stigma to identify the influence of public stigma, internalized stigma, self-esteem, and self-efficacy on recovery attitudes in individuals in inpatient treatment for AN. Using a cross-sectional design, 36 female participants with AN completed questionnaires during the first week of intensive inpatient treatment. Better attitude towards recovery was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 107 publications
(173 reference statements)
2
18
0
Order By: Relevance
“…As discussed in Truth 1, an eating disorder represents a health crisis that affects every aspect of an individual's life. In addition to myriad psychiatric and somatic complications and comorbidities enumerated in Truth 1, eating disorders also lead to considerable psychological distress, as well as isolation, stigmatization, and difficulties with family and other interpersonal relationships (Ali et al, ; Caslini et al, ; Dimitropoulos, McCallum, Colasanto, Freeman, & Gadalla, ; van Langenberg, Sawyer, le Grange, & Hughes, ). Further, eating disorders are associated with financial burden, delays in healthy development, and functional impairment and may interfere with social role functioning including intimate relationships, reproductive health and parenting (see summaries in Tables S2–S4).…”
Section: Truth 3: An Eating Disorder Diagnosis Is a Health Crisis Thamentioning
confidence: 99%
“…As discussed in Truth 1, an eating disorder represents a health crisis that affects every aspect of an individual's life. In addition to myriad psychiatric and somatic complications and comorbidities enumerated in Truth 1, eating disorders also lead to considerable psychological distress, as well as isolation, stigmatization, and difficulties with family and other interpersonal relationships (Ali et al, ; Caslini et al, ; Dimitropoulos, McCallum, Colasanto, Freeman, & Gadalla, ; van Langenberg, Sawyer, le Grange, & Hughes, ). Further, eating disorders are associated with financial burden, delays in healthy development, and functional impairment and may interfere with social role functioning including intimate relationships, reproductive health and parenting (see summaries in Tables S2–S4).…”
Section: Truth 3: An Eating Disorder Diagnosis Is a Health Crisis Thamentioning
confidence: 99%
“…Similarly, undiagnosed Latina women with ED symptomatology showed higher levels of stigmatisation of mental health treatment than women who reported a clinical history of EDs (Higgins, Bulik, & Bardone-Cone, 2016). A survey of women in inpatient treatment for AN found that higher public and internalised stigma predicted poorer attitudes to recovery (Dimitropoulos, McCallum, Colasanto, Freeman, & Gadalla, 2016). Two studies suggested the relationship between stigma and negative attitudes to help-seeking is particularly strong in men (Griffiths, Mond, Li, et al, 2015;Hackler et al, 2010).…”
Section: Self-stigmatisation and Illness Concealmentmentioning
confidence: 99%
“…One criticism is that most of this work has concentrated on psychotic or mood disorders such as schizophrenia or depression, while EDs have been relatively overlooked. The scarce research that has recently focused on ED stigma typically either examined just one ED (e.g., AN) [ 27 , 28 ]; did not necessarily distinguish between AN, BN, and BED; or addressed only a single aspect of ED stigma: either its content, its stigmatizing sources, or its consequences [ 4 , 7 , 42 ]. For example, the recent systematic review conducted by Foran et al [ 4 ] only investigated the consequences of ED stigma.…”
Section: Introductionmentioning
confidence: 99%